(untitled) (Conversatoria Linguistica, 2023)
State security management, like any organisation, requires not only the provision of appropriate forces and resources but also the proper transmission of information and messages. Only the ability to send and receive messages correctly ensures efficient implementation of assigned tasks, their understanding, and execution. For the process of managing them to proceed properly, it is essential to follow the rules of interpersonal communication. In this context, it is necessary to further define the elements of communication competence. They can be divided into five psychological and linguistic components. They are also determinants of proper communication (i.e. correct, appropriate, and at the same time effective). These include having a high level of communication awareness, presenting a high communication culture, active listening, using appropriate feedback, and avoiding communication barriers. The results of research on the communication competences of the surveyed students allow us to draw the conclusion that their level of communication awareness is too low, which is a quite a disturbing phenomenon, because it is the awareness of mistakes made or deficiencies and ignorance in the discussed area that is an essential element of improving communication competence. The multitude of aspects for which communication competences are of great importance is almost unlimited, and therefore emphasing the need for their guided development and improvement is a priority.